Yield and bunch stem/bunch ratio of 'Nanicão' bananas at different densities and arrangements - Kluge, Ricardo Alfredo; Filho, João Alexio Scarpare; Filho, Ricardo Victória; Jacomino, Angelo Pedro (Pesquisa Agropecuaria Brasileira, 2000)
This research was carried out with the objective to evaluate the effects of different densities and plant arrangement on components of yield and bunch stem/bunch ratio of 'Nanicão' banana established in Piracicaba, SP. Four densities (1,333, 1,666, 2,222 and 3,333 plants ha-1) and two arrangements (rectangle and triangle) were studied. Independent of arrangement the increase of density raised fruit yield of 37.24 to 75.83 t ha-1. However bunch mass was reduced of 30.30 to 24.79 kg due to reduced fruit mass. The bunch stem/bunch ratio was 8% independent of density and arrangement. At density of 3,333 plants ha-1 can be exported 6.80 t ha-1 of bunch stem of plantation and these component of yield can be used as raw material to manufacture paper.